Some aspects of online education training and retraining of physical education and sports - N. V. Filonenko; N. A. Ushakova (Путеводитель предпринимателя, 2020)
This article actualizes the problem of training and retraining of personnel in the physical education and sports industry. Based on the results of sociological surveys of students, the most acceptable time for conducting online classes is provided, as well as criteria for evaluating the quality of online lectures (webinars) formed by the authors to concentrate the attention of students during the classes.